ANALISIS USAHA BUDIDAYA TAMBAK BANDENG PADA TEKNOLOGI TRADISIONAL DAN SEMI_INTENSIF DI KABUPATEN KARAWANG - Mahfudlotul 'Ula; Nunung Kusnadi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2017)
The low productivity of milkfish produced by traditional technology encourage the development of new farming technologies to increase productivity. Semi-intensive technology has evolved since the 2000s. However, this technology increases the cost of production because of the additional input of artificial feed. One of the regencies which produce milkfish using both traditional and semi-intensive technology is Karawang Regency. The objective of this research were to analyze profit and cost efficiency in traditional and semi-intensive techonology. The method of data collection conducted purposive as many as 30 milkfish farmers with traditional technology and 33 milkfish farmers with semi-intensive technology. The results show that semi-intensive technology provides a higher level of productivity and higher profitability. However, traditional technology was more efficient than semi-intensive technology. This condition causes the milkfish cultivation with traditional technology are still exist because it provides a higher return to capital.